Bilateral post traumatic thalamic infarct - Sumeet Singh (Romanian Neurosurgery, 2014)
Bilateral thalamic infarction is rarely seen in cases with artery of Percheron embolization. Artery of Percheron is a rare variant of arterial supply to both thalamus and midbrain. Occlusion of this artery following trauma and causing bilateral thalamic infarction is rare and very few cases are reported in world literature.